Short Note: Cryptosporidium spp. oocysts detected using acid-fast stain in faeces of gentoo penguins ( Pygoscelis papua ) in Antarctica - Fredes, Fernando; Díaz, Angela; Raffo, Eduardo; Muñoz, Pamela (Antarctic Science, 2008)
Cryptosporidium is considered to be one of the indicators of environmental contamination and water quality (Garcia 2001, Fayer 2004, Ramirez & Sreevatsan 2006). At the present time the presence of this parasite has been recorded on all the continents, including Antarctica (Fredes et al. 2007a).